Chemistry of primary and secondary phases in intraplate basalts and volcaniclastic sediments at DSDP Leg 89 Holes - Peter A Floyd; G Rowbotham (PANGAEA, 1986)
Electron microprobe data are presented for clinopyroxenes, plagioclases, palagonites, smectites, celadonites, and zeolites in Hole 462A sheet-flow basalts and Site 585 volcaniclastic sediments. Glomerocrystic clinopyroxenes in Hole 462A are predominantly Ti-poor augites with minor fractionation to ferroaugites in rim portions. Quenched plumose clinopyroxenes show considerable variation from Ca-rich to Ca-poor augites, although all are characterized by being Tirich and Cr-poor relative to the glomerocrysts. Two differentiated series of Site 585 pyroxene compositions, calcic augite and diopside-salite, demonstrate the coexistence, in the vitric and lithic clasts, of tholeiitic and alkali basalt types, respectively. Plagioclase compositions in all samples are mainly labradorites, although some zoned Hole 462A glomerocrysts range from An73 to An20 and are characterized by high Mg and Fe contents in the more calcic varieties. The K content of the plagioclases is highest in the more sodic crystals, although the overall higher orthoclase component of Site 585 plagioclases reflects the generally higher bulk-rock K content. The compositions of both secondary smectites and celadonites are similar irrespective of the alteration location (glass, matrix, vesicles, etc.), although brown smectites replacing interstitial glass have marginally higher total Fe contents than pale green and yellow smectites. Analyzed zeolites are mainly phillipsites with variable alkali content, and, together with associated celadonite, represent late-stage alteration repositories for K under mildly oxidizing conditions. The compositions of both early and late secondary minerals are typical of those formed by the submarine alteration of basaltic rocks at low temperatures.
Supplement to: Floyd, PA; Rowbotham, G (1986): Chemistry of primary and secondary phases in intraplate basalts and volcaniclastic sediments, Deep Sea Drilling Project Leg 89. In: Moberly, R; Schlanger, SO; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 89, 459-470, https://doi.org/10.2973/dsdp.proc.89.116.1986